Identification of m6A Regulator-Associated Methylation Modification Clusters and Immune Profiles in Melanoma - Du, Fengying; Li, Han; Li, Yan; Liu, Yang; Li, Xinyu; Dang, Ningning; Chu, Qingqing; Yan, Jianjun; Fang, Zhen; Wu, Hao; Zhang, Zihao; Zhu, Xingyu; et al. (Frontiers in Cell and Developmental Biology, 2021)
RNA N6-methyladenosine (m6A) modification in tumorgenesis and progression have been highlighted and discovered in recent years. However, the molecular and clinical implications of m6A modification in melanoma tumor microenvironment (TME) and immune infiltration remain largely unknown. Here, we utilized consensus molecular clustering with nonnegative matrix factorization (NMF) based on the melanoma transcriptomic profiles of 23 m6A regulators to determine the m6A modification clusters and m6A-related gene signature. Three distinct m6A modification patterns (m6A-C1, C2, and C3), which characterized by specific m6A regulators expression, survival outcomes and biological pathways, were identified in more than one thousand melanoma samples. The immune profile analyses showed that these three m6A modification subtypes were highly consistent with the three known immune phenotypes: immune-desert (C1), -excluded (C2), and –inflamed (C3). Tumor digital cytometry (CIBERSORT, ssGSEA) algorithm revealed an upregulated infiltration of CD8+ T cell and NK cell in m6A-C3 subtype. An m6A scoring scheme calculated by principal component of m6A signatures stratified melanoma patients into high- and low-m6sig score subgroups; a high score was significantly associated with prolonged survival and enhanced immune infiltration. Furthermore, fewer somatic copy number alternations (SCNA) and PD-L1 expression were found in patients with high m6Sig score. In addition, patients with high m6Sig score demonstrated marked immune responses and durable clinical benefits in two independent immunotherapy cohorts. Overall, this study indicated that m6A modification is involved in melanoma TME immune regulation and contributes to formation of tumor immunogenicity. Comprehensively evaluation of the m6A modification pattern of individual tumors will provide more insights into molecular mechanisms of TME characterization and promote more effective personalized biotherapy strategies.